Refleksioon kui vahend ja lahendus Jeesus Siiraki Tarkuseraamatus - Jakobson, Jonas (Usuteaduslik Ajakiri, 2013)
Reflection as a Means and Solution in the Wisdom of Sirach One cannot help but marvel at the fact that the Hebrew poetic composition the Wisdom of Ben Sira (Sir) of such breadth and diversity of genre can be attributed to a single scribe – Jesus Ben Sira. This enables insight into the poetic composition not only on a scale of cola and bicola but also on a larger scale, behind which the grand intention of the scribe can be perceived. Although foreign influences can be detected in Sir, the most rewarding comparisons of the lines of content and structure has been presented with Pr, especially Pr 1–9. Albeit the use of different genres can be detected in Pr 1–9, e.g. didactic speech and didactic narrative, the breadth of Sir works in its favour, creating more ground for diversity – hymns, prayers and autobiographical poetic narratives. This article considers the three analysed poems all sharing the theme of “death” (Sir 40:11–17, 41:1–4 and 41:5–13) as belonging to the genre of didactic narrative. According to quantitative and semantic (repetitions and parallelism) traits, a precise logic can be detected working behind each poem. One may be able to detect an especially strong structural link between Sir 40:11 and 41:10, of which both rely heavily on parallelism. On the whole the use of didactic narrative in Sir serves as a means for achieving a uniform thematic and structural integrate composition in which the final vision of Ben Sira’s theology manifests itself.